To build a mobile application that runs on JAVA, that integrates same vital time consuming daily varsity tasks, running on a virtual server accessible to both the teacher and the students - Ahmed, Nazia; Saha, Biplob Kumar (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2009.